2005
DOI: 10.1007/s11104-004-1650-0
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to Soil Flooding–sensing and signal-transduction

Abstract: Flooding results in major changes in the soil environment. The slow diffusion rate of gases in water limits the oxygen supply, which affects aerobic root respiration as well as many (bio)geochemical processes in the soil. Plants from habitats subject to flooding have developed several ways to acclimate to these growth-inhibiting conditions, ranging from pathways that enable anaerobic metabolism to specific morphological and anatomical structures that prevent oxygen shortage. In order to acclimate in a timely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 120 publications
2
68
0
1
Order By: Relevance
“…In addition, we also noticed that CS greatly suppressed rice growth, with fewer and shorter roots than the control (Fig. 1b), which corresponds to previous studies (Visser and Voesenek 2005;Fukao and Bailey-Serres 2008).…”
Section: Cs Enhanced Fe and Mn Plaque Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, we also noticed that CS greatly suppressed rice growth, with fewer and shorter roots than the control (Fig. 1b), which corresponds to previous studies (Visser and Voesenek 2005;Fukao and Bailey-Serres 2008).…”
Section: Cs Enhanced Fe and Mn Plaque Contentsupporting
confidence: 90%
“…In addition to O 2 and CO 2 , another major gas regulator of rice in submergence responses, ethylene, accumulates continuously leading to a series of changes in plant morphological and anatomical traits (Visser and Voesenek 2005;Fukao and Bailey-Serres 2008). The ethylene concentration in the internodes of excised stem sections increased from 0.02 to 1 lL L -1 after 7 days of partial submergence and was blocked by amiooxyacetic acid or AVG and enhanced by ACC in the Bangladesh variety of floating rice (Métraux and Kende 1983;Raskin and Kende 1984).…”
Section: Cs Induces Expression Of Ethylene Synthesis Genes In Rice Rootsmentioning
confidence: 99%
“…Konings and Verschuren (1980) first reported that growth of maize in aerated but N-deficient nutrient solution resulted in the development of aerenchyma in roots. Studies with maize later confirmed that both low concentrations of N or low levels of P nutrition increased aerenchyma formation in roots (Drew et al 1989;Fan et al 2003;Visser and Voesenek 2004). Furthermore, when young maize plants were grown in a complete, well-oxygenated nutrient solution and then deprived of their external source of S, the treatment also induced the formation of aerenchyma in roots (Bouranis et al 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Aerenchyma is a parenchyma tissue that contains lacunae, created by lysigeny or schizogeny, and is formed during different environmental conditions such as oxygen shortage or deprivation of some nutrients (Drew et al 2000;Visser and Voesenek 2004;Haque et al 2010;Jiang et al 2010;Fagerstedt 2010). It aims to facilitate effective translocation of oxygen, carbon dioxide and ethylene or other gases, to redirect scarce resources or to provide a rapid diffusion path for solutes within the root cortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation